Galleria mellonella (Greater Wax Moth) as a Reliable Animal Model to Study the Efficacy of Nanomaterials in Fighting Pathogens - Stefania Villani; Matteo Calcagnile; Christian Demitri; Pietro Alifano (Nanomaterials)
The spread of multidrug-resistant microbes has made it necessary and urgent to develop new strategies to deal with the infections they cause. Some of these are based on nanotechnology, which has revolutionized many fields in medicine. Evaluating the safety and efficacy of these new antimicrobial strategies requires testing in animal models before being tested in clinical trials. In this context, Galleria mellonella could represent a valid alternative to traditional mammalian and non-mammalian animal models, due to its low cost, ease of handling, and valuable biological properties to investigate host–pathogen interactions. The purpose of this review is to provide an updated overview of the literature concerning the use of G. mellonella larvae as an animal model to evaluate safety and efficacy of nanoparticles and nanomaterials, particularly, of those that are used or are under investigation to combat microbial pathogens.